Transpiration and stomatal behaviour of Quercus ilex plants during the summer in a Mediterranean carbon dioxide spring (Plant, Cell & Environment, 1998)
Variations in the water relations and stomatal response of Quercus ilex were analysed under field conditions by comparing trees at two locations in a Mediterranean environment during two consecutive summers (1993 and 1994). We used the heat-pulse velocity technique to estimate transpirational water use of trees during a 5 month period from June to November 1994. At the end of sap flow measurements, the trees were harvested, and the foliage and sapwood area measured. A distinct environmental gradient exists between the two sites with higher atmospheric CO2 concentrations in the proximity of a natural CO2 spring. Trees at the spring site have been growing for generations in elevated atmospheric CO2 concentrations. At both sites, maximum leaf conductance was related to predawn shoot water potential. The effects of water deficits on water relations and whole-plant transpiration during the summer drought were severe. Leaf conductance and water potential recovered after major rainfall in September to predrought values. Sap flow, leaf conductance and predawn water potential decreased in parallel with increases in hydraulic resistance, reaching a minimum in mid-summer. These relationships are in agreement with the hypothesis of the stomatal control of transpiration to prevent desiccation damage but also to avoid ‘runaway embolism’. Trees at the CO2 spring underwent less reduction in hydraulic resistance for a given value of predawn water potential. The decrease in leaf conductance caused by elevated CO2 was limited and tended to be less at high than at low atmospheric vapour pressure deficit. Mean (and diurnal) sap flux were consistently higher in the control site trees than in the CO2 spring trees. The degree of reduction in water use between the two sites varied among the summer periods. The control site trees had consistently higher sap flow at corresponding values of either sapwood cross-sectional area or foliage area. Larger trees displayed smaller differences than smaller trees, between the control and the CO2 spring trees. A strong association between foliage area and sapwood cross-sectional area was found in both the control and the CO2 spring trees, the latter supporting a smaller foliage area at the corresponding sapwood stem cross-sectional area. The specific leaf area (SLA) of the foliage was not influenced by site. The results are discussed in terms of the effects of elevated CO2 on plant water use at the organ and whole-tree scale.

Vulnerability of xylem to embolism in relation to plant hydraulic resistance in Quercus pubescens and Quercus ilex co-occurring in a Mediterranean coppice stand in central Italy (New Phytologist, 1998)
The seasonal patterns of xylem embolism and xylem transport properties in Quercus pubescens Willd. and Quercus ilex L. trees growing in a natural mixed coppice stand in conditions of severe water stress were investigated. Xylem embolism was evaluated in both dehydrating branches and in apical twigs during a whole year. Measurements of xylem water potential were conducted from predawn to sunset on selected sunny days. On the same days, diurnal courses of leaf conductance were monitored. Measurements of half-hourly sap flow were made by the heat-pulse technique throughout the summer. At the onset of summer, a sharp decrease in water potential was observed in both species. Full recovery of water potentials was observed for both species after the first major rainfall event in September. Both experienced serious embolism throughout the year, ranging between minima of c. 60% (expressed as percentage loss of hydraulic conductivity) after the rains in autumn and after bud burst in spring, and maxima of c. 80% during summer and after freezing-thawing events during the winter season. A significant negative linear relationship was found between water potential and xylem embolism in branches dehydrating in air for Q. pubescens and Q. ilex. Q. pubescens had greater efficiency in hydraulic transport (higher specific conductivity and leaf specific conductivity) by the xylem than Q. ilex. In June, leaf conductance was high early in the morning and decreased gradually during the day. Midday depression of leaf conductance, as a result of high evaporative demand combined with water deficit, was observed in both species. In August, leaf conductance of both species was greatly reduced, as water potential dropped to extremely low values, and the stomata were almost completely closed during the afternoon. No hysteresis resulting from plant capacitance was observed in the relationship between shoot water potential and sap flow. Q. pubescens exhibited very high values of whole-tree hydraulic resistance between July and September, whereas Q. ilex generally showed lower values. The effect of soil moisture depletion on the relationship between sap flow and shoot water potential appears as a lowering of water potential at zero flow. A significant decrease of whole-tree hydraulic resistance in both species was observed with the onset of the autumn, preceding the partial recovery of twig hydraulic conductivity. The results demonstrate that both Q. pubescens and Q. ilex, although highly tolerant of severe water stress and tissue dehydration, operate at the limits of safety which are surpassed under severe droughts, and prolonged climatic stress might predispose these Quercus species to decline.

Water relations of oak species growing in the natural CO2 spring of Rapolano (central Italy) (Ann. For. Sci., 1996)
The effect of elevated atmospheric carbon dioxide on water relations was examined on downy oak (Quercus pubescens) and holm oak (Q ilex) trees. The study was conducted on trees growing in a naturally enriched CO2 spring. Sap velocity and sap flow were measured by the heat pulse technique. On the same trees, daily courses of xylem water potential, leaf conductance and transpiration were monitored. Plant water relations were evaluated by pressure-volume analysis method on shoots; on the same branches, relative conductivity of xylem was measured. Both species exhibited increased osmotic potential and decreased symplasmic fraction of water in trees adapted to increased CO2. Downy oak showed lower stomatal conductance under elevated CO2, but holm oak did not. Both species displayed higher sap flow in control trees. In both species, increased carbon dioxide did not influence xylem embolism formation.